Sex Differences in Risk Profile, Stroke Cause and Outcome in Ischemic Stroke Patients With and Without Migraine - Linstra, Katie M.; van Os, Hendrikus J. A.; Ruigrok, Ynte M.; Nederkoorn, Paul J.; van Dijk, Ewoud J.; Kappelle, L. Jaap; Koudstaal, Peter J.; Visser, Marieke C.; Ferrari, Michel D.; MaassenVanDenBrink, Antoinette; Terwindt, Gisela M.; Wermer, Marieke J. H. (Frontiers in Neuroscience, 2021)
Background – An increased risk of stroke in patients with migraine has been primarily found for women. The sex-dependent mechanisms underlying the migraine-stroke association, however, remain unknown. This study aims to explore these sex differences to improve our understanding of pathophysiological mechanisms behind the migraine-stroke association. Methods – We included 2492 patients with ischemic stroke from the prospective multicenter Dutch Parelsnoer Institute Initiative study, 425 (17%) of whom had a history of migraine. Cardiovascular risk profile, stroke cause (TOAST classification) and outcome (modified Rankin scale [mRS] at 3 months) were compared for both sexes between patients with and without migraine. Results – A history of migraine was not associated with sex differences in the prevalence of conventional cardiovascular risk factors. Women with migraine had an increased risk of stroke at young age (onset <50 years) compared with women without migraine (RR: 1.7; 95%CI:1.3-2.3). Men with migraine tended to have more often stroke in the TOAST category other determined etiology (RR: 1.7; 95%CI: 1.0-2.7) in comparison with men without migraine, whereas this increase was not found in women with migraine. Stroke outcome was similar for women with or without migraine (mRS ≥3 RR 1.1; 95%CI:0.7-1.5) whereas men seemed to have a higher risk of poor outcome compared to their counterparts without migraine (mRS ≥3 RR: 1.5; 95%CI:1.0-2.1). Conclusion – Our results indicate possible sex differences in the pathophysiology underlying the migraine-stroke association, which are unrelated to conventional cardiovascular risk factors. Further research in larger cohorts is needed to validate these findings.